2010
DOI: 10.3810/pgm.2010.05.2142
|View full text |Cite
|
Sign up to set email alerts
|

New Perspectives in Type 2 Diabetes, Cardiovascular Risk, and Treatment Goals

Abstract: Diabetes mellitus is a complex and increasingly common metabolic disease that is characterized by hyperglycemia and associated with microvascular and macrovascular complications. Approximately 90% of patients with diabetes have type 2 diabetes. Obesity and type 2 diabetes are intricately linked, with weight gain being a major contributor to the increasing incidence of type 2 diabetes. Both conditions are independent risk factors for cardiovascular disease, which is the cause of death for the majority (65%) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 78 publications
0
16
0
Order By: Relevance
“…Both are independent risk factors for the development of cardiovascular disease. 12 Difficulties in achieving weight loss may be partly cultural, and it has been shown that few overweight black women consider themselves overweight and that thinness is associated with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). 13 A Cape Town study of 240 black girls showed that two-thirds perceived fatness as a sign of happiness and wealth.…”
Section: Discussionmentioning
confidence: 99%
“…Both are independent risk factors for the development of cardiovascular disease. 12 Difficulties in achieving weight loss may be partly cultural, and it has been shown that few overweight black women consider themselves overweight and that thinness is associated with human immunodeficiency virus/acquired immunodeficiency syndrome (HIV/AIDS). 13 A Cape Town study of 240 black girls showed that two-thirds perceived fatness as a sign of happiness and wealth.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoglycemia is associated with negative impact, such as unpleasant and sometimes dangerous symptoms, weight gain (due to defense eating), deterioration of glycemic control (due to reduced adherence to therapy and therapeutic goals because of fear of new hypoglycemic episodes), increased cardiovascular risk and increased risk for microvascular complications [38][39][40][41] . Insulin therapy is associated with a high risk of hypoglycemia [29][30][31] .…”
Section: Hypoglycemiamentioning
confidence: 99%
“…Although structured education and life-style modifications are the basic pillars in managing T2DM, achieving and maintaining glycaemic control becomes a challenge as the condition progresses despite the availability and use of multiple glucose lowering therapies. 2 Moreover, the conventional therapies used in the management of T2DM can be associated with undesirable side effects such as hypoglycaemia and weight gain. However, treatment with GLP1RAs has the added benefit of weight loss and a low risk of hypoglycaemia in addition to improving glycaemic control.…”
Section: Introductionmentioning
confidence: 99%
“…1 This includes reduced insulin secretion from β-cells, increased glucagon production from α-cells, increased hepatic glucose output, increased lipolysis, increased renal glucose reabsorption, insulin resistance (in the periphery, where it reduces glucose uptake, and in the brain, where it promotes greater food intake), neurotransmitter dysfunction, and a reduced incretin effect. 1,2 Incretins are gut hormones produced from intestinal cells in response to oral glucose ingestion, which in turn stimulates insulin secretion. In people without diabetes, an oral glucose load elicits a greater insulin response than intravenous glucose administration, known as the "incretin effect".…”
Section: Introductionmentioning
confidence: 99%